2022
DOI: 10.3390/cells11213450
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Biological Evaluation of Melt-Electrowritten Polycaprolactone Scaffolds for Acetabular Labrum Restoration

Abstract: Repair or reconstruction of a degenerated or injured acetabular labrum is essential to the stability and health of the hip joint. Current methods for restoration fail to reproduce the structure and mechanical properties of the labrum. In this study, we characterized the structure and tensile mechanical properties of melt-electrowritten polycaprolactone scaffolds of varying architectures and assessed the labrum cell compatibility of selected graft candidates. Cell compatibility was assessed using immunofluoresc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…[16] Similarly, Santschi et al (2022) targeted mechanics representative of the soft tissues covering the acetabulum using sinusoidal MEW structures (Figure 3C), showing that primary labrum cells were able to migrate directly from the tissue specimen into the scaffolds. [116] Cell and subcellular scale morphology can be dictated by biomaterial surface modifications and the mechanical loading regimes applied during dynamic culture or in vivo environments can significantly modulate cell behavior. Mechanical loading of specifically designed scaffold architectures can therefore be leveraged as the driver for guiding cell alignment and stimulation of specific differentiation and matrix formation towards targeted tissue regeneration.…”
Section: Sinusoidal Architecturementioning
confidence: 99%
See 1 more Smart Citation
“…[16] Similarly, Santschi et al (2022) targeted mechanics representative of the soft tissues covering the acetabulum using sinusoidal MEW structures (Figure 3C), showing that primary labrum cells were able to migrate directly from the tissue specimen into the scaffolds. [116] Cell and subcellular scale morphology can be dictated by biomaterial surface modifications and the mechanical loading regimes applied during dynamic culture or in vivo environments can significantly modulate cell behavior. Mechanical loading of specifically designed scaffold architectures can therefore be leveraged as the driver for guiding cell alignment and stimulation of specific differentiation and matrix formation towards targeted tissue regeneration.…”
Section: Sinusoidal Architecturementioning
confidence: 99%
“…C) SEM image showing the architecture of wave-patterned scaffolds used for static and dynamic cell culture and fluorescent widefield microscopy images of actin-stained cells on wave-patterned scaffolds following long-term physiological stretching or static control. Adapted from Santschi et al(2022) (CC-BY) [116].…”
mentioning
confidence: 99%
“…The study showed that grid-like structures with decreasing fiber spacing exhibited favorable tensile properties and primary labrum cells were able to migrate into the scaffolds and grow in vitro. [16] 1.1.4. Meniscus Korpershoek et al created a meniscus scaffold tissue model suitable for one-stage cell-based treatment using MEW technology.…”
Section: Bone Tissuementioning
confidence: 99%
“…These kinds of scaffolds help to guide the cell growth in the direction of gradient immobilized over the scaffold. This will lead to the fabrication of in vitro model of different tissue as previously discussed in the literature for bone, [8][9][10][11][12] muscle, [14,15] nerve, [18,19] cartilage, [20,21] vascular, [13] acetabular labrum, [16] and meniscus. [17] This technique opens up a new avenue to utilize the architectural design variable in the favor of biological outcome by controlling the amount of attached EGF into the scaffolds and can be used for fabrication of in vitro model of tissue and tested in vivo in future.…”
Section: Postprocess Approachmentioning
confidence: 99%
See 1 more Smart Citation